1993
DOI: 10.1084/jem.177.5.1511
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced susceptibility of blood monocytes from patients with pulmonary tuberculosis to productive infection with human immunodeficiency virus type 1.

Abstract: Blood monocytes from patients with active pulmonary tuberculosis and age-matched healthy purified protein derivative-reactive donors were infected with human immunodeficiency virus type 1 (HIV-1)JR-FL in vitro to assess their susceptibility to productive infection by HIV-1. HIV-1 p24 levels (enzyme-linked immunosorbent assay) in supernatants of infected cells from patients with tuberculosis, albeit variable, were significantly higher at days 10-20 of culture; the maximum levels of p24 antigen were greater in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 17 publications
(32 reference statements)
2
52
0
Order By: Relevance
“…Early after the recognition that TB and HIV were converging to amplify the problems that each of the epidemics posed alone (231), peripheral blood monocytes from patients with active TB were found to be more susceptible to productive infection by HIV in vitro (247). Moreover, levels of HIV have been found to be higher in M. tuberculosis-infected regions of the lungs than in the uninvolved regions of the same patient (274).…”
Section: Tb Effects On Hiv: the Other Side Of The Cellular And Molecumentioning
confidence: 99%
See 1 more Smart Citation
“…Early after the recognition that TB and HIV were converging to amplify the problems that each of the epidemics posed alone (231), peripheral blood monocytes from patients with active TB were found to be more susceptible to productive infection by HIV in vitro (247). Moreover, levels of HIV have been found to be higher in M. tuberculosis-infected regions of the lungs than in the uninvolved regions of the same patient (274).…”
Section: Tb Effects On Hiv: the Other Side Of The Cellular And Molecumentioning
confidence: 99%
“…The development of TB is associated with increased HIV replication, as measured by the viral load at the site of TB infection in the lungs as well as by the plasma viral load (246,247). As described in more detail below, M. tuberculosis activates HIV transcription and enhances viral entry in vitro (55).…”
Section: Effect Of Tuberculosis On Hivmentioning
confidence: 99%
“…Mortality of dually infected HIV/tuberculosis individuals has been reported to be as high as 50% at 12 mo in New York compared to < 10% due to M. tuberculosis alone, and mortality among HIV-1-infected individuals with multidrug-resistant M. tuberculosis can be as high as 90% at 9 mo (13). Toosi et al (14) reported an enhanced susceptibility of blood monocytes from patients with tuberculosis to productive infection with Alveolar macrophages are primary players in host defense phagocytosing M. tuberculosis, and are capable of being infected by HIV-1. At sites of active M. tuberculosis infection, bacilli-laden macrophages may be HIV-infected as well.…”
Section: -263-8442mentioning
confidence: 99%
“…Isoniazid, by its ability to kill M. tuberculosis, obviates the host immune response to contain M. tuberculosis and thereby, lessens viral burden and prolongs HIV symptom-free interval and survival. Furthermore, the immune response during active tuberculosis has been shown to prime peripheral blood cells and enhance their susceptibility for HIV infection (Tossi et al 1993).…”
mentioning
confidence: 99%